Profesionalisme dan Ketepatan Waktu dalam Manajemen Pelayanan Publik - Aziza Bila; Wahib Assyahri (Journal of Education on Social Science (JESS), 2023)
In Public sector management, public service has the main goal to realize good service by equity theory. At this time, equity theory is considered relevant because it can describe the relationship between customer perceptions of the distribution of human resources (employees). This employee’s perceptions was demanded that the employees must exhibit their capability which representation through professionalism and timeliness of employees. The novelty of this research is responsiveness as an intervening variable to increase public service. The ability of the employee to solve customer problems also to be customer assessment of service quality, especially in terms of responsiveness. In-depth, good service describe an employee’s timeliness in responding to customer needs, which one aspect to realize customer satisfaction. The objective of this research is to prove the implementation of professionalism and timeliness in increasing customer satisfaction through responsiveness as an intervening variable. This research used a quantitative method with a survey strategy. The research is located at the Class II Immigration office of Agam, West Sumatera. Data was collected using a valid and reliable questionnaire. Then, Data was analyzed using path analysis. The result of the research explains that there are influences of professionalism and timeliness as direct and indirect toward customer satisfaction.